Adenine Phosphoribosyltransferase Deficiency: An Underdiagnosed Cause of Lithiasis and Renal Failure - Marra, Giuseppina (Springer Berlin Heidelberg, 2011)
We describe an infant affected by adenine phosphoribosyltransferase (APRT) deficiency diagnosed at 18 months of age with a de novo mutation that has not been previously reported. APRT deficiency is a rare defect of uric acid catabolism that leads to the accumulation of 2,8 dihydroxyadenine (2,8-DHA), a highly insoluble substance excreted by the kidneys that may precipitate in urine and form stones. The child suffered from renal colic due to a stone found in the peno-scrotal junction of the bulbar urethra. Stone spectrophotometric analysis allowed us to diagnose the disease and start kidney-saving therapy in order to avoid irreversible chronic kidney damage. APRT deficiency should always be considered in the differential diagnosis of pediatric urolithiasis.